Productive exposures: Vulnerability as a parallel practice of care in ethnographic and community spaces - Zizzo, Gabriella (The Australian journal of anthropology, 2021)
Theories of vulnerability are most often seen in the anthropology of disaster studies, where socio-economic and political inequalities produce environmental vulnerabilities, and the people situated in these locations are positioned as vulnerable and dependent 'Others'. Rather than reproduce vulnerability as a concept denoting weakness, this paper seeks to examine the generative capacities of vulnerability practised in parallel in ethnographic and community spaces. As a form of witnessing and participating in and out of differing social worlds, anthropology engages in different vulnerabilities with and between multiple actors. This paper examines how a community program working with families identified as 'disadvantaged' in South Australia strategically uses vulnerability as a productive resource and a practice of care. In theorising vulnerability through parallel practices in both ethnographic approaches and this community program, we argue that vulnerability can be leveraged away from negative welfare discourses towards alternative politics of radical care and social change.